2022
DOI: 10.1002/ajpa.24623
|View full text |Cite
|
Sign up to set email alerts
|

Do maternal grandmothers influence breastfeeding duration and infant nutrition? Evidence from Merida, Mexico

Abstract: Objectives: Breast-feeding is sensitive to somatic, hormonal, behavioral and psychological components of maternal capital. However, through grandmothering, older women may also influence breast-feeding by transferring informational resources to their daughters. We hypothesized that mothers with prolonged instrumental support from their own mother are more likely to have received advice and to have favorable attitudes/practices regarding breastfeeding, compared to those lacking such support, with implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 109 publications
0
1
0
Order By: Relevance
“…Indeed, previous studies conducted in Papua New Guinea, Guatemala, and Mexico have reported that grandmothers negatively influenced breastfeeding duration and exclusivity, which may provide some explanation for the current study's findings [36][37][38]. Grandmothers' attitudes towards and understanding of breastfeeding may present problems beyond nutritional health due to a lack of knowledge about current evidence-based breastfeeding practices, such as the early introduction of complementary foods to infants less than six months old [36,38].…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, previous studies conducted in Papua New Guinea, Guatemala, and Mexico have reported that grandmothers negatively influenced breastfeeding duration and exclusivity, which may provide some explanation for the current study's findings [36][37][38]. Grandmothers' attitudes towards and understanding of breastfeeding may present problems beyond nutritional health due to a lack of knowledge about current evidence-based breastfeeding practices, such as the early introduction of complementary foods to infants less than six months old [36,38].…”
Section: Discussionmentioning
confidence: 66%
“…They may also be due in part to who alloparents are. The effects of allocare by knowledgeable and experienced adults (e.g., grandmothers) may be different from those by less experienced individuals such as infant's siblings (Deang et al, 1988; Sear et al, 2000; Vázquez‐Vázquez et al, 2021; Vázquez‐Vázquez et al, 2022). While the existing literature is limited, studies have suggested that siblings can act as alloparents, aiding with infant care unless they are too young themselves to care for others (Helfrecht & Meehan, 2016; Kramer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%